Paul Gauguin and Victor Segalen: Aesthetic of Diversity between Writing and Painting - Mančić, Aleksandra (Porównania, 2016)
An example of modern thought on otherness is the one going across different cultures (transcultural) leading across different arts and different disciplines (transdisciplinary), tackling the issue fundamentally posed as an issue of travel as well as of translation (translational): the line that leads from the painter Paul Gauguin to the writer Victor Segalen in their search for new visions and reflections related to Exoticism and Primitivist art is a tentative response to the decline of diversity triggered by colonialism.